Therapeutic Targeting of Protein Kinase CK2 Gene Expression in Feline Oral Squamous Cell Carcinoma: A Naturally Occurring Large-Animal Model of Head and Neck Cancer(†) - Cannon, Claire M. (Hum Gene Ther Clin Dev, 2017)
Protein kinase CK2 (CK2) is a highly promising target for cancer therapy, and anti-CK2 gene expression therapy has shown effectiveness in rodent models of human head and neck cancer (HNC). To date, there has been no large-animal model of cancer in which to further explore anti-CK2 therapies. Feline oral squamous cell carcinoma (FOSCC) has been proposed as a large-animal model for human HNC, and we have previously shown that CK2 is a rational target in FOSCC. Here we have tested the hypothesis that a novel tenfibgen-coated tumor-specific nanocapsule carrying RNA interference (RNAi) oligonucleotides targeting feline CK2α and CK2α′ (TBG-RNAi-fCK2αα′) would be safe in cats with FOSCC; assessment of target inhibition and tumor response were secondary aims. Nine cats were enrolled and treated at two dose levels in a 3+3 escalation. Cats received a total of six treatments with TBG-RNAi-fCK2αα′. Pre- and posttreatment, tumor and normal oral mucosa biopsies were collected to assess CK2 expression, using immunohistochemistry (IHC) preparations evaluated by light microscopy. Toxicity and tumor response were assessed on the basis of standard criteria. The most common adverse events were grade 1 or 2 weight loss and anorexia. Grade 3 tissue necrosis was seen in association with tumor response in one cat, asymptomatic grade 4 elevations in aspartate transaminase and creatine phosphokinase in one cat, and asymptomatic grade 3 hypokalemia in one cat. Of six cats with evaluable biopsies, two had a reduction in CK2 IHC score in tumors after treatment. Four cats had progressive disease during the study period, three had stable disease, one had partial response, and response could not be evaluated in one cat. We conclude that the drug appeared safe and that there is some evidence of efficacy in FOSCC. Further investigation regarding dosing, schedule, target modulation, toxicity, and efficacy in a larger group of cats is warranted and may inform future clinical studies in human head and neck cancer.